Generation of transgenic cattle expressing human β‐defensin 3 as an approach to reducing susceptibility to Mycobacterium bovis infection. (30th January 2016) - Su, Feng; Wang, Yongsheng; Liu, Guanghui; Ru, Kun; Liu, Xin; Yu, Yuan; Liu, Jun; Wu, Yongyan; Quan, Fusheng; Guo, Zekun; Zhang, Yong
Abstract : Bovine tuberculosis results from infection with Mycobacterium bovis, a member of the Mycobacterium tuberculosis family. Worldwide, M. bovis infections result in economic losses in the livestock industry; cattle production is especially hard‐hit by this disease. Generating M. bovis ‐resistant cattle may potentially mitigate the impact of this disease by reducing M. bovis infections. In this study, we used transgenic somatic cell nuclear transfer to generate cattle expressing the gene encoding human β‐defensin 3 ( HBD3 ), which confers resistance to mycobacteria in vitro . We first generated alveolar epithelial cells expressing HBD3 under the control of the bovine MUC1 promoter, and confirmed that these cells secreted HBD3 and possessed anti‐mycobacterial capacity. We then generated and identified transgenic cattle by somatic cell nuclear transfer. The cleavage and blastocyst formation rates of genetically modified embryos provided evidence that monoclonal transgenic bovine fetal fibroblast cells have an integral reprogramming ability that is similar to that of normal cells. Five genetically modified cows were generated, and their anti‐mycobacterial capacities were evaluated. Alveolar epithelial cells and macrophages from these cattle expressed higher levels of HBD3 protein compared with non‐transgenic cells and possessed effective anti‐mycobacterial capacity. These results suggest that the overall risk of M. bovis infection in transgenic cattle is efficiently reduced, and support the development of genetically modified animals as an effective tool to reduce M. bovis infection. Abstract : Bovine tuberculosis (TB) infections cause significant economic losses in the livestock industry. In an effort to generate TB‐resistant cattle, Zhang and colleagues used somatic cell nuclear transfer to generate genetically modified cattle expressing human β‐defensin‐3 (HBD3), which confers resistance to mycobacteria in vitro . Alveolar epithelial cells and macrophages − the primary defences against inhaled Mycobacterim bovis − from these cattle expressed higher levels of HBD3 and possessed effective anti‐mycobacterial capacity. These results suggest that the overall risk of M. bovis infection in transgenic cattle is efficiently reduced and support the development of genetically modified animals as an effective tool to reduce M. bovis infection.